Effect of soluble interleukin-6 receptor α and interleukin-6 secreted by polymorphonuclear leukocytes on tumor necrosis factor-α expression and its production by peripheral blood mononuclear cells - E. Jablonska (Hindawi Limited, 2002)
Background: It has recently been shown that soluble interleukin-6 receptor (sIL-6R) alone or complexed with interleukin (IL)-6, besides their regulatory role in a wide variety of both normal and abnormal biologic reactions mediated by IL-6, could be an effective stimulator of the cell function.